2014
DOI: 10.1089/jmf.2013.2763
|View full text |Cite
|
Sign up to set email alerts
|

Raspberry Ketone Promotes the Differentiation of C3H10T1/2 Stem Cells into Osteoblasts

Abstract: The decrease in the bone mass associated with osteoporosis caused by ovariectomy, aging, and other conditions is accompanied by an increase in bone marrow adipose tissue. The balance between osteoblasts and adipocytes is influenced by a reciprocal relationship. The development of modalities to promote local/systemic bone formation by inhibiting bone marrow adipose tissue is important in the treatment of fractures or metabolic bone diseases such as osteoporosis. In this study, we examined whether raspberry keto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The multipotent stem cell line C3H10T1/2, which has the potential to be differentiated into adipocytes, chondrocytes, osteocytes or myocytes [24], is a widely used model to study the modulations of stem cell fate under nutritional and environmental influence [2529]. Consistent with the effects of parabens on 3T3-L1 adipocyte differentiation [14], butylparaben markedly promoted adipogenic differentiation (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…The multipotent stem cell line C3H10T1/2, which has the potential to be differentiated into adipocytes, chondrocytes, osteocytes or myocytes [24], is a widely used model to study the modulations of stem cell fate under nutritional and environmental influence [2529]. Consistent with the effects of parabens on 3T3-L1 adipocyte differentiation [14], butylparaben markedly promoted adipogenic differentiation (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…This cell line was chosen for its maintained capacity to differentiate into different tissues such as bone, cartilage, adipose tissue, etc. , Shea demonstrated that BMP2 treatment of C3H10T1/2 mesenchymal stem cells induces both chondrogenesis and osteogenesis. Takata used them to evaluate the potential of a specific ketone found in raspberries to promote osteogenesis. In the present study, it should be specified that the C3H10T1/2 were seeded on the scaffold in the absence of any differentiation factor to avoid any guided differentiation toward bone lineage that could be only to the result of the presence of BMP2.…”
Section: Discussionmentioning
confidence: 99%
“…Raspberry volatiles are important for the perception of sensory quality (odor, flavor) and for mold resistance [ 13 ], and some are claimed to have nutraceutical properties [ 28 , 29 ], although the nutritional role of volatile compounds is still very controversial. Fruit volatile compounds are influenced by numerous factors including cultivar variation, climate, soil, ripeness, and many other variables [ 11 , 19 , 30 ].…”
Section: Volatile Compounds In Raspberrymentioning
confidence: 99%